Agroforestry Landscape Patterns and Carbon Storage towards Optimal Land Planning and Utilization in Sipolha Horisan Village, Pamatang Sidamanik District, Simalungun Regency - Tri Astuti; Tioner Purba; Athoriq Hafiz (Jurnal Penelitian Pendidikan IPA, 2026)
Land conversion due to the increasing population growth rate for various interests has impacted forest land, and deforestation has become a global problem. One step that can be taken in regional planning to utilize and manage forest resources based on the landscape is to develop an agroforestry system. Agroforestry is a method of land management that combines (mixed use) forest plants with agricultural crops or livestock farming within a single area. One area that utilizes land through an agroforestry system is Sipolha Horisan Village, Pamatang Sidamanik District, Simalungun Regency. The purpose of this study was to determine the plant species’ composition and agroforestry landscape pattern in Sipolha Horisan Village. The results showed that the agroforestry system practiced by farmers was agrisilvicultural agroforestry, with a random pattern. Carbon storage potential is influenced by plant growth rates. At the tree level, the biomass was 313.18 tons/ha and carbon stocks were 144.06 tons/ha. For understory plants, the biomass was 19.89 tons/ha and carbon stocks were 9.15 tons/ha. The litter produced 39.77 tons/ha of biomass and carbon stocks were 18.29 tons/ha.